Tom Clancy's Op-center - Clancy, Tom, 1947-2013 and Pieczenik, Steve (London HarperCollins, 1995)
The first volume in the bestselling series of high-tech, high-action thrillers created by Tom Clancy and Steve Pieczenik -- repackaged in a stunning new-look cover.
Keywords: Crisis management in government -- United States